Experimental and theoretical correlation of very intense visible green photoluminescence in BaZrO3 powders - Cavalcante, L. S.; Longo, V. M.; Zampieri, M.; Espinosa, J. W. M.; Pizani, P. S.; Sambrano, J. R. [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Simoes, M. L.; Paskocimas, C. A. (American Institute of Physics (AIP), 2008)
Very intense visible green photoluminescence (PL) was observed at room temperature in structurally ordered-disordered BaZrO3 powders. Ab initio calculations, ultraviolet-visible absorption spectroscopy, electron paramagnetic resonance, and PL were performed. Theoretical and experimental results showed that local defects in the cubic structure caused by [ZrO5 center dot V-O(z)] complex clusters, where V-O(z) = V-O(x), V-O(center dot), and V-O(center dot center dot), play an important role in the formation of hole-electron pairs, giving rise to a charge gradient in the structure which is responsible for PL emission. (c) 2008 American Institute of Physics.